The factors associated with workforce attrition and intention-to-leave among healthcare workers in New Zealand: a systematic literature review and meta-synthesis of qualitative research - Mia Clarke; Ben Stephen; Mike Frecklington; Irene Zeng; Matthew R Carroll; Richard J Siegert; Sarah Stewart (Frontiers in Organizational Psychology, 2026)
Despite growing concern about the stability of New Zealand's (NZ) health workforce, no prior synthesis has examined qualitative evidence on factors associated with attrition or intention-to-leave. This systematic review and meta-synthesis included 20 studies and followed the ENTREQ checklist to guide a content analysis of the literature. Seven themes were generated spanning organizational, professional, and personal levels: high workloads, unsupportive organizational culture, limited opportunities for career advancement, inadequate remuneration, a decline in professional identity, negative impacts on wellbeing, and work-life imbalance. The findings demonstrate that attrition and intention-to-leave arise from cumulative pressures across these levels, highlighting the need for coordinated retention strategies that address all domains of work experience.